Strategi Adaptasi dan Keberlanjutan Usaha Mikro Informal: Analisis Empiris pada Pelaku Usaha Cilok di Kawasan Urban - Angelica Natasha; Danang Yudha Prakasa (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
Cilok, a widely consumed Indonesian street food predominantly produced from tapioca flour, represents an important source of affordable snacks for urban and peri-urban communities. Beyond its cultural popularity, cilok plays a strategic role in supporting local food security and the sustainability of Small and Medium Enterprises (SMEs). This study aims to analyze the contribution of SMEs in the cilok market by examining their role in providing low-cost nutritional alternatives, sustaining informal economic activities, and promoting inclusive economic growth. Employing a qualitative research design, data were collected through in-depth interviews with cilok street vendors and complemented by a structured review of relevant academic and policy-oriented literature. The findings indicate that cilok-based SMEs contribute significantly to urban livelihoods by offering accessible food products with relatively stable demand and low production costs. However, the study also identifies several structural challenges, including limited access to capital, inconsistent product quality, low nutritional diversification, and weak compliance with food safety standards. Despite these constraints, there are substantial opportunities for product innovation, such as the incorporation of protein-rich ingredients, improved processing techniques, and basic nutritional labeling to enhance consumer trust and market competitiveness. This research underscores the importance of targeted policy interventions, capacity-building programs, and nutritional awareness initiatives to strengthen the resilience and sustainability of cilok SMEs. By positioning cilok not only as a traditional snack but also as a potential vehicle for affordable nutrition, this study contributes to the broader discourse on informal food systems, microenterprise development, and urban food accessibility in developing economies.